Relationship between sense of coherence and health-related behaviours in adolescents and young adults: a systematic review - Henrique da-; Rafael del-; Pedro Ángel Palomino-Moral; Catalina López Martínez; Sara Moreno-Cámara; Antonio Frías-Osuna (BMC, 2022)
Abstract Background The sense of coherence is developed through the learning process and contributes to the positioning of individuals in the health-disease continuum, facilitating successful and adaptive personal outcomes. Health-related behaviours represent a health determinant of utmost importance for public health and the development of adolescent and youth health promotion policies, as they are related to the main risk factors and problems of morbidity and mortality in our society. Previous studies have analysed the relationship between sense of coherence and only some individual health outcomes such as oral health, the relationship of sense of coherence with smoking and alcohol consumption, concluding that salutogenic factors are related to quality of life and preventive behaviours. The aim of this systematic review was to describe the relationship of sense of coherence with different health-related behaviours investigated so far in the adolescent and youth population. Methods A systematic review was carried out in databases (PubMed, CINAHL, Scopus and PsycInfo) and in the bibliographies of the retrieved articles, without limitation of time or language. Associations between sense of coherence and health-related behaviours have been assessed. Results A total of 1214 investigations were reviewed and 21 of them were included in this systematic review. The relationship between sense of coherence and eight health-related behaviours were identified (alcohol use, physical activity, tobacco use, eating habits, rest periods, use of illegal substances, behaviours related to oral health and time spent in games on the computer). Conclusions Our results increase the available evidence and support the solid relationship of the sense of coherence with health behaviours both as a protective factor against risk behaviours and for its positive association with preventive and health promoting behaviours of adolescents, young adults and university students.